THE ANTIOXIDANT EFFECTS OF CAPPARIS OVATA AND DEFERASIROX IN PATIENTS WITH THALASSEMIA MAJOR - Handan Duman; Duran Canatan; Guchan Alanoglu; Recep Sütçü; Tufan Nayır (Mediterranean Journal of Hematology and Infectious Diseases)
Ironoverload and auto-oxidation of unpaired globin chains are  the main causes of oxidative stress inpatients with thalassemia major. In thepresent study, we aimed to investigate the antioxidant effects of capparisovatta and deferasirox in thalassemic patients.A total 40  patients with thalassemia major aged between7-30 years, who have  been taken  regular red cell transfusion  and chelation (Deferasirox:30 mg/kg/day) forone  year are involved. They were dividedinto two groups as control and  studygroup randomly. Both study and control  groupswere followed by  regular  transfusion and chelationtherapy. In addition study group have been taken the marmalade of driedcapparis ovata   the breakfast with a  daily dose of 12.5 gryounger than 10 years and 25 gr older than 10 years for 6 months. Hematological, biochemical parameters,ferritin at every month and antioxidant enzymes (MDA, CAT, GPX, SOD) were measuredat the beginning and at the end of the study. There was  a significant difference between initial andfinal parameters  of the MDA levels instudy group. SODlevels  also decreased statistically in bothof the groups, CAT  and GPX levels didn’tdecrease significantly  in both of thegroups. Ferritin levels declinedsignificiantly both in control and study group. As conclusion,  our findings suggest that combination of  capparis  ovata with deferasirox  may   have additive effecton decreasing the oxidative damage and hepatoxicity.  This is preliminary work, it needs further works.